Analisis kesesuaian materi IPA dengan tujuan kurikulum pada buku teks pelajaran IPA SMP/MTS kelas VIII semester 1 untuk diintegrasikan dengan materi banjir - Mimo Putra Ardiansyah; Ahmad Fauzi; Yulkifli Yulkifli (Universitas Negeri Padang, 2019)
Indonesia is an archipelago prone to disasters such as floods hydrometeorologi. The impact posed by floods almost every year has increased both from loss of life, property or damage to public facilities. One of the causes of the large number of casualties happened i.e. lack of knowledge or understanding of the disaster. So the effort to reduce the impact of the flood disaster that is through education that is integrated with the material glut. This is in accordance with changes in education standards suggesting that the structure of the curriculum for the education unit was the appropriate education with potential local or excellence an area. One of the potential areas that are owned by the province of West Sumatra is disastrous floods. However, the fact there has been no real outstanding textbooks that have been integrated with the material of the flood. So the need for analysis of the suitability of the material science material with flooding. Before integrating the material into a flood of material need for the science analysis of the suitability of the material of the science on a textbook lesson in IPA with the purpose of the curriculum, for the Government's efforts in revising the curriculum lead to changes of national standards Education so that changes the structure and arrangement of the material in the textbook lessons. Then the results of the analysis of the suitability of the material science with the goal of this curriculum is to be used as an ingredient or material that will be seen the suitability of material science material with flooding. Type of this research is descriptive research with qualitative approach. The subject of this research is a textbook lesson in science class VIII semester 1 in books K and E. sampling Technique used was purposive sampling. Instruments for collecting data consists of sheets of material suitability analysis IPA with the goal of curriculum textbook lessons IPA SMP/MTs class VIII semester 1 and sheet material suitability analysis IPA with the material glut. The research results obtained are the suitability of a textbook lesson science SMP/MTs class VIII semester 1 with the goal of curriculum to book K obtained percentage for compliance 79.36% (accordingly) and the book E obtained percentage conformance 88,57% (very appropriate) . Then the level of conformity of the material science class VIII semester 1 with the flood of material on KD 3.1 is inappropriate category with 26.67 KD 3.2 is 66.67% with appropriate categories, KD 3.3 is 20% with a category is not appropriate, KD 3.4 and KD 3.6 are 33,33% with categories is inappropriate, KD 3.5 was 46,67% with quite appropriate category.